Flexible pressure visualization equipment for human-computer interaction. (March 2023) - Bi, S.; Jin, W.; Han, X.; Metts, J.; Ostrosky, A.D.; Lehotsky, J.; He, Z.; Jiang, C.; Asare-Yeboah, K.
Abstract: Flexible electronic technology has made great achievements in the past decade, and with the emergence of electronic skin inspired by human skin and epidermal electronics implanted into animal skin, great value has been demonstrated in wearable devices and soft robots. These technologies are based on a variety of flexible sensors, especially pressure sensors. It is worth noting that, in addition to continued improvements in the sensing ability of pressure sensors, the integration of various visualization modules with pressure sensors is still an important area of research in the pursuit of expanded application scenarios for flexible technologies and richer human-computer interaction. These integrated pressure visualization devices need to have flexibility, pressure sensing ability and obvious visual display at the same time. This is a challenge for thin film devices with simple structures. As the thickness of integrated devices increases significantly, new processes and materials with better flexibility are needed to ensure good contact between devices and human skin. With the advancement of flexible pressure sensing modules and the development of various visualization technologies based on electroluminescent and electrochromic principles, pressure visualization devices with unique patterning and self-powering properties are emerging. This paper summarizes the key progress surrounding integrated pressure sensing and visualization technology in recent years, and presents its prospective development direction and challenges.